Hyperglycemia-induced oxidative stress in isolated proximal tubules of mouse: the in vitro effects of myricitrin and its solid lipid nanoparticle. (3rd September 2021) - Ahangarpour, Akram; Oroojan, Ali Akbar; Khorsandi, Layasadat; Kouchak, Maryam; Badavi, Mohammad
Abstract: Context: The hyperglycemia (Hyper) induces oxidative stress in kidney tubular cells. Myricitrin (Myr) has an antioxidant effect along with low bioavailability. Objective: The present research investigated the effects of Myr and its solid lipid nanoparticles (SLN) on isolated proximal tubules exposed to the hyperglycemic condition. Materials and Methods: In this experimental study, the proximal tubules of mice were dissected by the microdissection method and the tubules were prepared for experimental or Real Time-PCR measurement. Results: The malondialdehyde level, transforming growth factor-β, nuclear factor kappa B and Bax genes expression increased in Hyper and decreased in Hyper + Myr and its SLN-treated groups compared to Hyper. Superoxide dismutase, total antioxidant capacity, the viability of proximal tubules and Bcl-2 gene expression decreased in untreated Hyper and increased in all treatment groups compared to Hyper. Conclusion: The hyperglycemia-induced oxidative disorder, inflammation and apoptosis in proximal tubules and that administrating Myr and its SLN improved them.